Majelis Sholawat Al-Banjari: Etno-Religius dan Identitas Urang Banjar Perantauan Di Serdang Bedagai - Aulia Rahmi; Faisal Riza; Ismail; Rholand Muary; Muhammad Jailani (Getpress Management Journals, 2025)
This study aims to examine the role of the Majelis Sholawat Al-Banjari (MSB) within the Banjar community in Serdang Bedagai. MSB has become an essential part of Banjar identity, which is widely recognized as a community deeply devoted to shalawat, influenced by the teachings of Tuan Guru Syaikh Zaini bin Abdul Ghani (Abah Guru Sekumpul). This research employs a qualitative method with an ethnographic approach, involving participatory observation and the researcher’s direct engagement in MSB activities. The findings reveal that the etno-religious identity of the Banjar people in Serdang Bedagai has long been shaped by the tradition of Aruh Maulud, practiced well before the establishment of MSB. The presence of MSB has further reinforced this identity through the recitation of Maulid Simtudduror. Beyond serving as a medium for preserving religious traditions, MSB also functions as a space that strengthens the ties of Banjar migrants and acts as a “reminder” of their ancestral homeland in Kalimantan. This etno-religious identity becomes even more deeply embedded through the practice of shalawat inherited from Abah Guru Sekumpul, making shalawat not only a form of spiritual expression but also a symbol of the Banjar people’s collective identity in Serdang Bedagai.